Psychiatric disorders in urology patients – a review of the literature - Czernikiewicz, Andrzej; Wisz, Beata (Current Problems of Psychiatry, 2012)
The purpose of this study was to analyze the existing literature regarding patients’ mental disorders after urological treatment. Special attention was paid to problems of patients with cancer, treated surgically, and with andropause and intimate problems. Mental disorders occurring in the course of somatic diseases may be a reaction to the disease itself, its severity, nuisance, and limitations coming along with the disease. It may also be a result of poor prognosis, as well as significant change of social situation, and the outcome of somatic factors influencing the central nervous system. Also it may be a combination of two mentioned above conditions. Cancer, due to its stereotypical social perception, is mainly identified with death in agony, which can be an enormous psychological burden, even though it may not cause any limitation to physical or social activities. Many surgical procedures are associated with particularly high anxiety. The issue of andropause, called simultaneously the male midlife psychoendocrine syndrome is also associated with changes in the psyche, and patients intimate sphere. Taking into consideration urological aspect, sexual disorders occurring after surgery can be a consequence of invasive treatment. These disorders affect both men and women, although the literature devoted to women’s sexual disorders with purely urological problems is poor. Reduced sexual ability can lead to various disorders, complex and reduced self-esteem; for instance: psychosomatic, depressive and neurotic disorders, relationship and interpersonal problems, low patience. Based on the literature, it can be concluded that patients undergoing urological treatment are facing various psychological or psychiatric disturbances. These problems are often margina-lized in somatic medicine. In many cases setting proper diagnosis is difficult due to similarity of symptoms that occur in both disturbances: urological, and psychiatric. It is worth to carry on the therapy holistically, combining psychological and somatic symptoms.